2013
DOI: 10.1042/cs20120661
|View full text |Cite
|
Sign up to set email alerts
|

Protection from age-related increase in lipid biomarkers and inflammation contributes to cardiovascular protection in Gilbert's syndrome

Abstract: Recent epidemiological and clinical data show protection from CVD (cardiovascular disease), all-cause mortality and cancer in subjects with GS (Gilbert's syndrome), which is characterized by a mildly elevated blood bilirubin concentration. The established antioxidant effect of bilirubin, however, contributes only in part to this protection. Therefore we investigated whether mildly elevated circulating UCB (unconjugated bilirubin) is associated with altered lipid metabolism. The study was performed on GS and ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
81
1
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(101 citation statements)
references
References 38 publications
14
81
1
3
Order By: Relevance
“…This was also indicated by a negative association between UCB and BMI. The impact of lipid metabolism and a generally lower lipid profile in Gilbert syndrome subjects might also be related to the lower BMI, what was recently shown by our group (16,41). Another observation showed that weight loss was associated with increasing bilirubin levels and was more likely in men (42).…”
Section: Discussionmentioning
confidence: 59%
“…This was also indicated by a negative association between UCB and BMI. The impact of lipid metabolism and a generally lower lipid profile in Gilbert syndrome subjects might also be related to the lower BMI, what was recently shown by our group (16,41). Another observation showed that weight loss was associated with increasing bilirubin levels and was more likely in men (42).…”
Section: Discussionmentioning
confidence: 59%
“…Hence, it is conceivable that anti-inflammatory and anti-oxidative effects of bilirubin may both contribute to less low-grade chronic inflammation in MetS [3,15,18,25,26,40]. The only study available so far showed that SAA tended to be lower in subjects with isolated hyperbilirubinemia due to Gilbert syndrome compared to healthy individuals [17], suggesting that high bilirubin levels could be implicated in lower SAA levels. In the current study, the relationship of SAA with bilirubin was modified by insulin and HOMA-IR, but not by elevated glucose.…”
Section: Discussionmentioning
confidence: 91%
“…Little information is, however, available concerning relationships with other inflammatory markers [17]. The pro-inflammatory protein, serum amyloid A (SAA), is able to impair anti-oxidative properties of high density lipoprotein (HDL) [18][19][20], thereby contributing to increased oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…Findings from in vivo studies show that higher than normal STB levels are strongly associated with liver-related mortality. On the other hand, a growing body of evidence suggests now that bilirubin is an important antioxidant that has several protective functions and STB levels were reported to be inversely associated with the risk of CVD (Djousse et al 2001;Vitek et al 2002;Lin et al 2006;Vitek 2012;Agrawal and Sharma 2015), arterial calcification and stiffness (Tanaka et al 2009;Zhang et al 2012;Li et al 2013), atherosclerosis (Novotny and Vitek 2003;Oda 2014;Tatami et al 2014), inflammation (Erdogan et al 2006;Vitek and Schwertner 2007;Maruhashi et al 2012;Wallner et al 2013), insulin resistance (Lin et al 2009), and cancer mortality (Temme et al 2001;Li et al 2015). Some authors suggest that increased bilirubin levels in healthy subjects are linked to low cancer mortality, especially among older men, probably because the antioxidant activity of this Unauthenticated Download Date | 5/10/18 10:49 PM pigment can help protect against ROS and cancer, which means that measurements of serum bilirubin concentrations might contribute to cancer risk estimation (Temme et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with elevated STB levels tend to have lower levels of total cholesterol, LDL, and triglycerides but Unauthenticated Download Date | 5/10/18 10:49 PM higher levels of HDL, and HDL-cholesterol is an independent negative risk factor for cardiovascular mortality . Serum bilirubin level within the normal range has been shown to be inversely related to the ApoB/ApoA-1 ratio (Wallner et al 2013), which is considered to be a superior parameter for predicting the risk of cardiovascular events as it reflects the cholesterol transport and has been shown to be strongly related to some CVD risk factors and cardiovascular events such as myocardial infarction and stroke (Walldius et al 2004;Sniderman et al 2006;Lima et al 2007). Furthermore, some authors suggest that elevated serum bilirubin levels in hyperbilirubinemic subjects are associated increased activity of endothelial nitric oxide synthase (eNOS), which stimulates vasodilatation and is a fundamental determinant of cardiovascular homeostasis (Kundur et al 2015).…”
Section: Discussionmentioning
confidence: 99%